POTENSI KEKERASAN GENDER BERBASIS ONLINE PADA PENYALAHGUNAAN TEKNOLOGI KECERDASAN BUATAN BAGI PEREMPUAN DI MEDIA - Rachmaria, Laksmi; Andy Susanto (Jurnal Netnografi Komunikasi, 2024)
This research uses a qualitative approach with descriptive methods and data collection techniques in the form of literature studies. Research results: apart from providing convenience, artificial intelligence technology also has negative impacts, one of which is related to online gender violence against women, including harassment and intimidation. AI can be used to automate online attacks such as verbal harassment, threats or intimidation, for example through chatbots used to send derogatory messages to women repeatedly, thereby creating an unsafe atmosphere in cyberspace. AI can also be misused in the distribution of revenge porn images and videos by digitally manipulating images or videos of women, so that they can be used as a tool to blackmail or humiliate them. AI can also be used to monitor female victims' online behavior, for example social media stalking and exploiting that information to carry out further attacks. Women who are victims of online gender violence often experience stigma and serious psychological impacts, such as anxiety disorders, depression and social isolation. Conclusion: collaboration between governments, online platforms, human rights activists and civil society is urgently needed to address the problem of online gender violence and its impact on women. Education and awareness about the threats associated with online gender violence is urgently needed.